"EVERY SPERM IS SACRED": PALESTINIAN PRISONERS, SMUGGLED SEMEN, AND DERRIDA'S PROPHECY. (November 2019) - Hamdan, Mohammed
Abstract: This paper investigates the contemporary phenomenon of smuggling sperm from within Israeli jails, which I treat as a biopolitical act of resistance. Palestinian prisoners who have been sentenced to life-imprisonment have recently resorted to delivering their sperm to their distant wives in the West Bank and Gaza where it is then used for artificial insemination. On the level of theory, my analysis of this practice benefits from Jacques Derrida's commentary in The Post Card on imaginative postal delivery of sperm to distant lovers. I use Derrida's heteronormative implication to examine how Palestinian prisoners defy the Israeli carceral system via the revolutionary act of sperm smuggling. The article then argues that smuggling sperm challenges the conventional gender codes in Palestinian society that see women in passive roles. Drawing on Derrida's metaphorical connection between masturbation and writing, I problematize the perception of speech/orality as primary in traditional Palestinian culture. Women, who mostly act as smugglers, become social agents whose written stories of bionational resistance emerge as a dominant mode of representation.